2017
DOI: 10.1017/dmp.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Evaluation of Personal Protective Ensembles Recommended for Use in West Africa

Abstract: Heat stress and PPE training, as well as the implementation of a work-to-rest ratio that avoids dehydration and possible heat stress issues, are recommended. (Disaster Med Public Health Preparedness. 2017;11:580-586).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…Similar result was found by MacFarlane, Chapman, Benke,et al (2008) where they found , up to 10-40% of farmers routinely do not use PPE at all 10 . Besides discomfort, PPE introduces additional physiological burden to the user in terms increase in heat stress, heart rate and core temperature significantly 11 . This could affect compliance to the recommended PPEs unless there is system for cooling the room.…”
Section: Figure 1 Problem Of Ppe Usage Discussionmentioning
confidence: 99%
“…Similar result was found by MacFarlane, Chapman, Benke,et al (2008) where they found , up to 10-40% of farmers routinely do not use PPE at all 10 . Besides discomfort, PPE introduces additional physiological burden to the user in terms increase in heat stress, heart rate and core temperature significantly 11 . This could affect compliance to the recommended PPEs unless there is system for cooling the room.…”
Section: Figure 1 Problem Of Ppe Usage Discussionmentioning
confidence: 99%
“…This is an important issue given that comfort can influence both PPE use compliance and duration of work cycles. [1,2] An oft-cited contributor to respiratory protective equipment-related discomfort is the perception of increased warmth, either regional (i.e., facial area) or global. [1] Recently, much interest has been directed towards the role of powered air-purifying respirators (PAPRs) in healthcare settings during infectious disease outbreaks, based upon multiple advantageous features, [3] including possible amelioration of some heat-related issues via cooling effects of PAPR air currents.…”
Section: Introductionmentioning
confidence: 99%
“…(27) It is easy to demonstrate that work with protective equipment against biological hazard complicates technical procedures; however, so far, no extensive studies have shown that the use of PPE requires highly intense physical effort that prohibits working for large time intervals. (28) We can conclude that the parameters studied reveal a metabolic pattern of poor physiological tolerance after the use of individual protection equipment level D in the observed sample. Consequently, future studies could derive a predictive rule that allows us to assess which professionals may tolerate and adapt better to work in a biological incident.…”
Section: Discussionmentioning
confidence: 56%